ANALISIS PEMASARAN RUMPUT LAUT (EUCHEUMA SP) DI DESA WUAKERONG KECAMATAN NAGAWUTUNG KABUPATEN LEMBATA - Petrus Rajamuda Kolly Dasion; Eri Yusnita Arvianti; Ana Arifatus Sa’diyah (Universitas Tribhuwana Tunggadewi, 2014)
Seaweed in Wuakerong Village, Nagawutung Sub District, Lembata Regency has prospects and business opportunities are adequate to give hope to farmers in improving welfare. The fact that seaweed farming has not yet provided better and maximum results as desired by the farmers. This study aims to evaluation the marketing channels, marketing margins and profit share of marketing agencies. The research is located in Wuakerong Village, Nagawutung Sub District, Lembata Regency which is determined purposively. The number of sample is 30 farmers taken by simple random sampling, 4 middlemen traders and 2 gatherer traders taken by using snowball method. The data collection methods is interview and questionnaire directly to farmers and marketing agencies, literary method or data collecting from institutions related to the research’s aims. The variables observed covered the condition of location, population, level of education, land, production, sale price, purchase price, marketing margin, profit share of marketing agencies, and marketing margins distribution. The research results show that there is two marketing channel in the researched result, as follows: Channel I : farmers middlemen traders gatherer traders PAP Channel II : farmers gatherer traders PAP The magnitude of marketing margins is different between the marketing channels, and so it is with profit share of marketing agency. On channel I, magnitude margin is IDR 3,250 and profit share is 71.11% on farmers, 17.76% on middlemen and 11.09% on gatherer traders. On channel II, the magnitude of marketing margin is IDR 1,250 and profit share is 88.88% on farmers and 11.09% to gatherer traders